Peer tutoring in EFL higher education: Exploring students’ learning through the lens of Vygotsky’s Zone of Proximal Development - Eko Purwanti; Ghani Rifqi Adli; Endro Dwi Hatmanto; Noor Qomaria Agustina (Teaching English as a Foreign Language Journal, 2026)
English plays a crucial role in Indonesian higher education; however, traditional classroom practices often limit opportunities for personalized learning and active student engagement. This study examines peer tutoring as an alternative approach, drawing on Vygotsky’s Zone of Proximal Development (ZPD), which conceptualizes learning as the progression from what learners can do independently to what they can achieve with guidance from More Knowledgeable Others (MKO). Employing a qualitative design, this research explores how peer tutoring supports English language learning in an English Language Education Department at a private university in Yogyakarta. Two main themes emerged from the findings. First, peer tutoring fosters both cognitive and socio-affective development, as students demonstrate enhanced critical thinking, increased motivation, greater confidence, and stronger collaborative relationships within a supportive learning environment. Second, peer tutoring operationalizes ZPD through a structured scaffolding process, beginning with diagnosing learners’ current abilities (Zone of Current Development) and advancing their competence toward independent performance (Zone of Actual Development) through guided interaction, explanation, modelling, and feedback. This study contributes to the growing body of research on student-centered learning by demonstrating how peer tutoring functions as an effective pedagogical strategy that integrates sociocultural theory into practical classroom contexts, particularly in EFL higher education settings.